Analysis conversational of children with cerebral palsy: study a multiple cases - Cesa, Carla Ciceri; Motta, Helena Bolli; Brandão, Lenisa (Research, Society and Development, 2020)
Introduction: The Speech-language Pathologist can and should contribute more actively and more theoretically grounded in the linguistic aspects of the use of alternatives to oral communication. Aim: To examine the conversational pattern of children with cerebral palsy and their communicative partners in Speech, Language and Hearing Science sessions. Method: A multiple, descriptive, cross and contemporary case study. Results: The communicative means used by children and partners were the verbal, verbal assisted, gestural, vocal and pictographic ones. It was observed thatrequest/answer and order/execution adjacent pairs were more commonly successful with clear evidence that they are more dependent linguistically on their conversational partners. Conclusions: The linguistic competence development seems to be favored by the Speech, Language and Hearing Science therapist when he reduces the number of response possibilities and at the same time makes the Augmentative and Alternative Communication resource available for expression by the child.